MIER3在结直肠癌中的表达及其相关蛋白的生物信息学分析 (Nan Fang Yi Ke Da Xue Xue Bao, 2017)
OBJECTIVE: To explore role of MIER3 gene in the development and progression of human colorectal carcinoma (CRC)and analyze the proteins that interact with MIER3 using bioinformatic techniques. METHODS: MIER3 mRNA and protein expressions were detected in 8 CRC biopsy samples and paired adjacent tissues using real-time PCR and Western blotting. Arecombinant eukaryotic expression vector pcDNA3-MIER3 was constructed and its effect on the proliferation and invasion of CRC cells were tested using CCK8 assay and Transwell migration assay. Bioinformatic methods were used to predict and analyze MIER3-interacting proteins. RESULTS: MIER3 was obviously down-regulated in the 8 CRC tissues as compared with the paired adjacent tissues. In human CRC cell line DLD1, MIER3 overexpression induced by transfection of the cells with pcDNA3-MIER3 significantly inhibited the cell proliferation and suppressed cell invasiveness in vitro. Bioinformatics analyses indicated that NAT9 was a potential MIER3-interacting protein and MIER3 was probably associated with tumor susceptibility. CONCLUSION: MIER3, which is obviously down-regulated in CRC tissues, is closely associated with the proliferation and invasion of CRC, and NAT9 protein is a probable MIER3-interacting protein